Development of the radiation and magnetic field tolerant DC/DC converter system for the ATLAS ITk Strip Detector. (1st January 2023) - Dyndał, M.; Cieśla, K.; Dąbrowski, W.; Górnicki, E.; Guguła, K.; Kopeć, R.; Koperny, S.; Korba, A.; Krzempek, D.; Stanecka, E.; Wiącek, P.; Wolter, M.
Abstract: The radiation and magnetic field tolerant step-down DC/DC converter system is developed to supply low-voltage power for the ATLAS ITk Strip Detector. The system is modular and consists of custom designed crates with embedded cooling plates, backplane, and DC/DC converter modules. Each converter module comprises two or four power channels. Each channel comprises a 48-to-11 V DC/DC converter, hardware overcurrent and overvoltage protection circuits, correction circuitry to compensate for voltage drops along the cables, and control and monitoring functionality based on the AMACStar chip. We present the design and performance of such a DC/DC converter system, including evaluation of its radiation tolerance.